2011
DOI: 10.1364/oe.19.013793
|View full text |Cite
|
Sign up to set email alerts
|

Multi-modal transmission of microwaves through hole arrays

Abstract: The microwave transmission through hole arrays in thick metal plates for both large holes (cut-off below onset of diffraction) and small holes (cut-off above onset of diffraction) have been compared through both experiment and modelling. Enhanced transmission is in part mediated by the excitation of diffractively coupled surface waves. Large holes, with cut-off below the onset of diffraction (due to the hole periodicity), are able to support multiple modes in transmission when the depth of the holes is suffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…31 Here, we utilize the enhanced EM transmission effect, in which the role of SPPs has been well studied, 23,29,30 to detect this dispersion. 32,33 This method facilitates our simulation because it does not need any prisms, and the dispersion of spoof SPPs can be directly observed from the transmission spectra.…”
Section: A Structurementioning
confidence: 99%
See 1 more Smart Citation
“…31 Here, we utilize the enhanced EM transmission effect, in which the role of SPPs has been well studied, 23,29,30 to detect this dispersion. 32,33 This method facilitates our simulation because it does not need any prisms, and the dispersion of spoof SPPs can be directly observed from the transmission spectra.…”
Section: A Structurementioning
confidence: 99%
“…13 When c ¼ 0, the cutoff wavelength of the degenerated 61 modes is given by k c ¼ 2pan=1:841 ¼ 15:87 mm, 33 where n ¼ With the cutoff frequencies f c known, we then try to fit the lowest transmission branches obtained in the COMSOL simulation. Here, as an approximation, we neglect the coupling between the upper and lower interfaces, and only consider the influence of the square lattice that folds k jj into the first Brillouin zone by k fng jj ¼ k jj À n 2p d .…”
Section: Dispersion Of Spoof Sppsmentioning
confidence: 99%
“…However, it has been recently shown [14,15] that periodic structures with very simple polarization insensitive scatterers such as subwavelength circular holes can be applied to control polarization response. The origin of the effect is enhanced transmission phenomenon [19][20], which can lead to enhanced polarization conversion [14,15]. For the goal one need to real-ize a regime of coupling of the incident wave with different type symmetry eigenmodes [21,22], leading to polarization sensitive enhanced transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the dip of 0.483 THz can be regarded as the high-order mode excited by the high oblique incidence of TM waves. 20,21) To sum up, we have investigated the mode properties of 3D-MWMs under oblique incidence by experiment and numerical. The results demonstrated that the MWMs show different responses for the TE and TM waves with the changes in the incident angle.…”
mentioning
confidence: 99%